Barriers, drivers and prospects of the adoption of artificial intelligence property valuation methods in practice. (4th May 2021) - Abidoye, Rotimi; Ma, Junge; Lee, Chyi Lin
ABSTRACT: Embracing technological advancement in the property valuation practice is unavoidable. However, studies show that valuers largely still adopt traditional methods of valuation. Hence, this study investigates the barriers, drivers, and prospects of the adoption of artificial intelligence (AI) valuation methods in practice. An online questionnaire survey was conducted on valuers practising in Australia. Their opinions about the topic were collected and analysed using frequency distribution and mean score ranking to establish the most significant factors. According to the valuers, the most important advantage of AI valuation methods is that they will help to reduce the cost of valuations. It was also found that the professional bodies that regulate the property valuation practice are the major driver of the adoption of AI valuation methods. The valuers expressed that AI valuation methods may produce accurate estimates. The valuers confirmed that the main prospect of adopting the AI valuation methods in practice is that it could transform the property valuation industry. It is evident that all the property valuation stakeholders should invest efforts in promoting the adoption of AI valuation methods in practice to bridge the gap between theory and practice. This will help reposition the property valuation profession.